창의,융합 과정으로서의 독서,작문교육과 테크놀로지 - 노명완; Myeong Wan Noh (독서연구, 2015)
20세기 전반부 심리학자들은 인간심리를 과학적, 객관적으로 연구한다면서 인간심리를 세분화, 유목화하였다. 그런데 그 결과는 오히려 비과학화와 비인간화를 가져왔을 뿐이다. 창의성은 심리학자들의 최대의 연구 관심사였지만, 이들의 방법론인 유목화로는 창의성을 포착할 수가 없었다. 그래서 당시 학자들은 창의성을 신비한 무의식적 작용으로 치부해 버렸다. 20세기 후반부에 들어서면서 심리학자들은 인간심리의 작용을 실제 측면에서 관찰하기 시작하였고, 그 결과 인간의 심리 작용은 모두 무엇인가(의미,지식, 정보, 감정, 느낌 등 인지적 정의적 모든 것)를 처리하는 과정이고, 그 핵심이 바로 의미.지식의 처리인 것을 확인하였다. 그래서 이들은 인간심리의 작용을 ‘의미구성’이라 불렀다. 이것이 바로 20세기 후반부에 출현한 구성주의이다. 의미의 구성은 그것 자체가 바로 지식의 생산 즉 창의이다. 이런 창의적사고 활동 중에서 가장 핵심적인 사고가 바로 인간의 언어사용이고, 그 중심에 독서와 작문이 있다. 그런데 학교 교과 중 국어과는 인간의 언어사용을 핵심 지도 내용으로 삼고 있다. 그런 점에서 국어 교과는 가장 창의적인 교과라 할 수 있다. 컴퓨터, 인터넷, 스마트폰 등과 같은 테크놀로지의 발전으로 문식환경이 크게 변하였다. 한편으로는 가용 지식 자원이 무한대로 넓어졌지만, 다른 한편으로는 그 지식 자원에 대한 신뢰가 크게 의심되고 있다. 그래서 테크놀로지의 사용에 대한 교육이 절실하다. 또 다른 한편으로는 테크놀로지의 발전으로, 지금까지 깜깜한 블랙박스라고 생각했던 인간 두뇌 속에서의 의미구성, 지식처리의 과정을 조금은 들여다볼 수 있게 되었다. 그 덕에 독서와 작문 교육에서는 개별화 지도도 쉬워졌고, 특히 과정 지도가 조금은 수월하게 되었다. Psychologists in the first-half of 20th century criticized their former psychologists of 19th century in that they investigated human mind very subjectively and on their own insights. Instead, the 20th century psychologists tried to analyze the whole mind into small constructing factors, and made a structural taxonomy. They declared their research methods as objective and scientific. But the so-called their scientific research methods only brought in unscientific, unobjective results. Despite of the endeavoring efforts to look into human mind through small windows of taxonomy, they only got lost the human mind itself, resulting huge segments of mind, so-called the psychological factors of activities. The creativity of human mind also got lost in their research. Psychologists in the second-half of 20th century got back in their research attitude. They just tried to observe what the students really did when they read or wrote. The results of the observation was quite simple: Students wanted to produce/understand the message (content, idea, knowledge, information, etc.) through language. This finding was the starting point of cognitive, social, and social-cultural research approaches of human mind, the so-called constructionism. Meaning construction is in itself a process of knowledge production. Reading process is knowledge production process through meaning construction, and writing process is also the same. The problem-solving processes of three school subjects (science, mathematics, and Korean language) tests clearly manifested some evidences in two aspects: The first is that subjective answering test is much better than the multiple choice test in terms of higher order thinking and creativity. The second is that the subjective answering test in reading/writing requires the most creative higher order level of thinking skills, just like the analysis, synthesis, evaluation. But the multiple choice test of reading/writing requires only the worst creative thinking, just as recognition skills. The technological development in recent years―like computer, internet, smartphone―changed the whole literacy environment. The resources of knowledge and information were expanded unlimitedly, but the reliability and validity of the knowledge/information in the internet world also got downed unlimitedly. It is quitely required that students need good teaching about what the internet world they are in is, about how to evaluate the knowledge and information in the internet, and also about how to use the reading/writing related technologies. One decisive advantages of technological development is that it can follow and investigate the tracks of reading/writing processes in the brain. Now it is quite possible to guide students to look into their own mental processes when they read or write.